العلاقات الليبية الدبلوماسية مع الدول العربية والأفريقية: قضايا وتحديات - غلالي، نضر (Ahmad Ibrahim Kulliyyah of Law, International Islamic University Malaysia, 2018)
Diplomacy plays an active role in supporting international relations, even if there are fewer common factors linking countries to each other, and there are successful examples of Arab countries and the Islamic world in this field. However, the conflicts of the Arabic world and African world are made by external parties whose purpose is to dismantle these countries from each other. The Islamic forces must serve as protector forces to the Arab world, not a rival working against it. Meanwhile, African wealth should also open its door to the Arab and Islamic countries to raise itseconomy. Therefore, the principle of dialogue and understanding among these countries should prevail for better relations in a world where conflicts are increasing, there are many changes and disturbances, and rights and facts are lost.